DNA metabarcoding of faecal pellets reveals high consumption of yew (Taxus spp.) by caribou (Rangifer tarandus) in a lichen-poor environment - Greniqueca Mitchell; Paul J. Wilson; Micheline Manseau; Bridget Redquest; Brent R. Patterson; Linda Y. Rutledge (Canadian Science Publishing, 2022)
Woodland caribou (Rangifer tarandus caribou) are threatened in Canada because of the drastic decline in population size caused primarily by human-induced landscape changes that decrease habitat and increase predation risk. Conservation efforts have largely focused on reducing predators and protecting critical habitat, whereas research on dietary niches and the role of potential food constraints in lichen-poor environments is limited. To improve our understanding of dietary niche variability, we used a next-generation sequencing approach with metabarcoding of DNA extracted from faecal pellets of woodland caribou located on Lake Superior in lichen-rich (mainland) and lichen-poor (island) environments. Amplicon sequencing of fungal ITS2 region revealed lichen-associated fungi as predominant in samples from both populations, but amplification at the chloroplast trnL region, which was only successful on island samples, revealed primary consumption of yew (Taxus spp.) based on relative read abundance (83.68%) with dogwood (Cornus spp.; 9.67%) and maple (Acer spp.; 4.10%) also prevalent. These results suggest that conservation efforts for caribou need to consider the availability of food resources beyond lichen to ensure successful outcomes. More broadly, we provide a reliable methodology for assessing ungulate diet from archived faecal pellets that could reveal important dietary shifts over time in response to climate change.